War in the air, 1914-45 - Murray, Williamson; Keegan, John, 1934- (London : Cassell, 1999)
Explores how airplanes were used in World War I and World War II.
Illustration on end-papers.
Includes bibliographical references (p. 216-217) and index.
Adult
Keywords: Air warfare -- History; World War, 1914-1918 -- Aerial operations; World War, 1939-1945 -- Aerial operations; Air warfare -- History; World War, 1914-1918.; World War, 1939-1945 -- Aerial operations